Endoscopic management of large ileocecal valve lesions over an 18-year interval - Ponugoti, Prasanna L.; Broadley, Heather M.; Garcia, Jonathan; Rex, Douglas K. (Endoscopy International Open, 2019)
Background and study aims Ileocecal valve (ICV) lesions are challenging to remove endoscopically. Patients and methods This was a retrospective cohort study, performed at an academic tertiary US hospital. Sessile polyps or flat ICV lesions ≥ 20 mm in size referred for endoscopic mucosal resection (EMR) were included. Successful resection rates, complication rates and recurrence were compared to lesions ≥ 20 mm in size not located on the ICV.Results During an 18-year interval, there were 118 ICV lesions ≥ 20 mm with mean size 28.6 mm (44.9 % females; mean age 71.6 years), comprising 9.03 % of all referred polyps. Ninety ICV lesions (76.3 %) were resected endoscopically, compared to 91.3 % of non-ICV lesions (P < 0.001). However, in the most recent 8 years, successful EMR of ICV lesions increased to 93 %. Conventional adenomas comprised 92.2 % of ICV lesions and 7.8 % were serrated. Delayed hemorrhage and perforation occurred in 3.3 % and 0 % of ICV lesions, respectively, compared to 4.8 % and 0.5 % in the non-ICV group. At first follow-up, rates of residual polyp in the ICV and non-ICV groups were 16.5 % and 13.6 %, respectively (P = 0.485). At second follow-up residual rates in the ICV and non-ICV lesion groups were 18.6 % and 6.7 %, respectively (P = .005). Conclusions Large ICV polyps are a common source of tertiary referrals. Over an 18-year experience, risk of EMR for ICV polyps was numerically lower, and risk of recurrence was numerically higher at first follow and significantly higher at second follow-up compared to non-ICV polyps.